Insulin Modulates NK Cell Activity in Liver Fibrosis MASH Patients via the STING Pathway - Johnny Amer; Ahmad Salhab; Amiram Ariel; Rifaat Safadi (Cells)
Background: The STING (Stimulator of Interferon Genes) pathway plays a vital role in the body’s innate immune defense system, primarily involved in DNA sensing and type I interferon production. While STING is well-established in various immune cells, its role in natural killer (NK) cells, particularly within the context of liver fibrosis, remains inadequately explored. Aim: The current study investigates the relationship between STING expression, NK cell activity, and insulin receptor (IR) signaling in patients with metabolic dysfunction-associated steatohepatitis (MASH). Methods: Peripheral NK cells were isolated from healthy controls and MASH patients with varying stages of liver fibrosis (early: F1/F2; advanced: F3/F4). The expressions of STING, IR, NK cell activation markers (CD107a, NKp46), and NK cell inhibitory markers (LAIR-1, Siglec-7) were assessed using flow cytometry. NK cell cytotoxicity against primary hepatic stellate cells (pHSCs) was evaluated through apoptosis assays. STING agonists (2′3′-cGAMP and DMXAA) were used to stimulate NK cells, and their effects on STING expression, NK cell activation, and cytotoxicity were measured. Additionally, the impact of insulin signaling on STING expression and NK cell function was examined. Results: Our results demonstrate that STING expression in NK cells correlates with disease severity in liver fibrosis. NK cells from MASH patients with advanced fibrosis (F3/F4) showed inhibited STING protein levels that were statistically comparable to healthy NK cells and accompanied by impaired cytotoxicity and decreased IFN-γ production. In contrast, NK cells from early fibrosis (F1/F2) exhibited higher STING expression and better functional activity. STING agonist treatment (2′3′-cGAMP) restored STING expression and enhanced NK cell activity across all fibrosis stages. Furthermore, insulin treatment and combined insulin and 2′3′-cGAMP treatment synergistically upregulated both IR and STING expressions, leading to improved NK cell function and increased cytotoxicity, particularly in advanced fibrosis. Conclusion: Our results highlight the potential of targeting STING and insulin signaling pathways as a therapeutic approach in restoring NK cell function and enhance immune surveillance in liver fibrosis.